Stacking of 2D materials via self-assembly - Rengasamy, Lingeshvaram (My University, 2025)
Remarkable physical and chemical properties of 2-dimensional transition metal carbide and nitride are grabbed much attention among the nanomaterials researchers. MXene, a new fascinating family of 2D transition metal carbides, nitrides, and carbonitrides. MXene has recently acknowledged significant attention due to its unique combination of properties such as large interlayer spacing, hydrophilic nature, excellent thermal stability, and high electrical conductivity, which proposed to be promising materials in many applications such as supercapacitor, solar cell, sensor, battery, water purification, sensor and electronic devices. Intriguing property value of Titanium carbide (MXene), convergence and adaptability of application in next generation devices is developing thin film technology. From the produced MXene nano sheets, using its nature of hydrophilic quality approached in self-assembly mechanism. Bottom up strategy of liquid-liquid interfacial have been puzzling the monolayers film formation based on different substrates. Here, interfacial tension in between two immiscible solvents is responsible for self-assembly because of its spontaneous ordering of 2D MXene in lateral structure. Flat surfaced substrate is used to transfer the self-assembled monolayers, then the fabricated MXene on substrates of surface morphology is examined in optical microscope, and Scanning electron microscope. From the inspections, it is clear based on the collection sped and time the size of the MXene can be varied in different size. In this regard, stacking the low dimensional materials such as homogenous MXene, chemical vapor deposited Graphene on copper substrate, and mixture of MXene-Graphene Oxide composite were investigated in this project.
Keywords: MXene; Nanofabrication; Stacking; 2D materials; Interfacial self-assembly; Energy storage